Cultivating Safety in the Information Technology Era - Endah Kumala Dewi; Fathul Himam; Achmad Sobirin (Faculty of Psychology, Universitas Gadjah Mada, 2020)
In the information technology era, the banking industry must compete in an external environment characterized by high levels of uncertainty, complexity and change. Accidents in high-risk manufacturing organizations are generally related to safety studies. The researcher attempted to study